The electronic fetal monitoring and the apgar of the newborn infant in the Hospital Regional Hermilio Valdizán. Huánuco, 2017 - Alvarado-Calixto, Nílton O. (2019)
Objective: To determine the relation ship between the electronic fetal monitoring (non stress test) antepartum and the Apgar of the newborn infant in the Hospital Regional Hermilio Valdizán of Huánuco between the months of September to ecember of the year 2017. Meth- odology: The type of research is observational, prospective, cross-sectional, correlational and explanatory scope. The sample is a non-probabilistic, constituted by a selected group of 150 pregnant women in low and high risk l. Results: The non-stress test was active reagent in 133 (88.67%) and active not reactive in 17 (11.33%), the score of the Apgar score of the newborn infant was 8 to 10 in 134 (89.33%) and from 0 to 7 in 16 (10.67%). Obtaining a Chi squared value of 3.32, which is lower than the critical Chi square, accepting the null hypothesis (Ho) of the non-existence of relationship between these variables. The diagnostic discrimination of the non-stress test is given by a sensitivity of 33.33%, specificity of 90.29%, positive predictive value of 23.53% and negative predictive value of 90.97%. Conclusions: There is no correlation between the non-stress test and the Apgar of the newborn, and that the test is more useful to rule out to diagnose fetal hypoxia.